Magyar László, Zettner Ede, Váncza Mihály (iratok) - Magyar László, Zettner Ede, Váncza Mihály (Fond 4 Lampel [Wodianer] Könyvkiadó Vállalat irattára, 1903)
Fond 4 Lampel [Wodianer] Könyvkiadó Vállalat irattára